Sustainable development through policy integration in Latin America: A comparative approach - Laura Rival (United Nations Research Institute for Social Development (UNRISD), 2012)
Whereas sustainable development used to be conceptualized in relation to differentiated development stages and contrasts between "consumer" and "basic needs" societies (Redclift 1991), the emerging green economy has internalized the new geopolitical conditions created by "globalization". Latin American countries, for instance, have characteristics of both "consumer" and "basic need" societies. Their challenge today is in large part similar to that of developed countries, in that they too need to translate socioeconomic development objectives into a model that maintains ecosystem services, biodiversity and low carbon emissions to support Earth Stewardship (Chapin et al. 2011). This paper examines how social and political actors in Brazil and in Ecuador propose to govern natural resource use sustainably, and how they work at building an alternative political economy based on ecosystem protection, biodiversity, renewable energy use and poverty reduction. The first case study shows how sustainable development is being reinvented by Brazilian grassroots organizations working in partnership with government agencies at various levels (municipal, state and federal) and with large Brazilian companies such as Braspetro. Nominated for a Global Award last year, this project combines popular education with a whole range of environmental conservation programmes to address structural poverty and environmental degradation in a semi-arid region from which people have had to migrate in order to survive. Through its holistic approach to sustainability in a municipality of around 38,000 inhabitants, the project has created the conditions for the flourishing of a local economy based on family farming and local services. It has already inspired other municipalities, both in the Amazon region (in Brazil and in neighbouring Spanish-speaking countries) and in Mozambique and other locations in Africa. This project illustrates the fundamental role played by small and medium-sized towns in creating resilient socioecological systems in the tropics. It also demonstrates the ways in which engaged citizenship can deepen the quality and the meanings of 'development'...
Keywords: 330